2012
DOI: 10.5812/ircmj.1302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Presence of Epstein Barr Virus in Nodal and Extra Nodal Diffuse Large B Cell Lymphoma of Head and Neck, an Iranian Experience

Abstract: BackgroundEpstein Barr Virus (EBV) is one of the most common viral infections in human population. EBV has a significant role in pathogenesis of Hodgkin's lymphoma, Burkitt's lymphoma and nasopharyngeal carcinoma. The role of EBV in non-Hodgkin’s lymphoma, diffuse large B cell (NHL - DLBL) in the head and neck is controversial.ObjectivesThe purpose of this study is to find out the difference between the presence of Epstein Barr virus in nodal and extra nodal lymphoma of head and neck.Patients and MethodsA tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
4
14
1
Order By: Relevance
“…The study results indicated higher positive results for these antibodies by ELISA in ALL group. Also, in the study conducted by Ashraf et al, (2012) presence of EBV, LMP gene were investigated in diffuse large B cell (DLBL) patients by Immune-Histo-Chemical (IHC) and PCR. The results reveal 10% prevalence of LMP by PCR in DLBL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study results indicated higher positive results for these antibodies by ELISA in ALL group. Also, in the study conducted by Ashraf et al, (2012) presence of EBV, LMP gene were investigated in diffuse large B cell (DLBL) patients by Immune-Histo-Chemical (IHC) and PCR. The results reveal 10% prevalence of LMP by PCR in DLBL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of EBV detection in this study was found to be high, and was similar to a Nigerian study which reported 54.5% EBV-positivity in all lymphomas [ 32 ]. This can be attributed to a similarity in the types of lymphomas and subtypes evaluated, as well as the extent of immune suppression of the study population [ 33 ]. The EBV positivity rate in NHL was slightly higher than that in HL, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of EBV positivity for NHL cases in this study was similar to those reported in Brazil, Uganda and Nigeria, which reported rates from 54.5% to 79.8% [ 9 , 22 , 32 ]. This similarity can be ascribed to the anatomical site or types of lymphomas evaluated [ 33 ]. The rate of EBV in lymphomas is also dependent on the overall rate of EBV infection in a specific geographical region.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology is still unknown, however, environmental agents and viruses, especially EBV, or vaccination, have been proposed to play a role in the pathogenesis of LCH ( 3 , 4 ). The role of EBV, as the etiologic agent of several malignancies is known and Herpes viruses are shown to be responsible for persistent infection ( 9 , 11 , 12 ). In addition, EBV and CMV are considered to be responsible for the hemophagocytic syndromes in human, with several inherited immunodeficiencies ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies, from various parts of the world, have reported the association of Epstein-Barr virus (EBV) infection with several malignancies and LCH, representing a possible etiologic role or contribution to its pathophysiology ( 3 , 4 , 9 - 12 ). However, other studies have failed to support these findings and the possible etiologic role of EBV and other viruses in LCH remains debated ( 13 - 16 ).…”
Section: Introductionmentioning
confidence: 99%